(untitled) (Nexo Revista Científica, 2021)
In the present paper is exposed the study of the rainfall patter distribution at Airport Managua pluviograph station. The study objective was determining the rainfall hyetographs and the advanced coefficients for the storm at each quartile, in the period 2002-20016. The rainfall accumulated curve mass were estimated for the storms with depth greater than 20 mm and duration less or equal to two h. The rainfall accumulated curve mass were normalized with respect theirs duration and precipitation depth. Forward, the rainfall distribution pattern were obtained for the storms with depth greater than 20 mm and for the storms with depth greater than 30 mm, which could be used for the estimates of maximum discharges to determines floods at Managua airport station influence area. The study suggests that the rainfall distribution patter obtained en both cases, it is not symmetric and differs from that obtained with the alternate blocks method.